2010
DOI: 10.3892/ijo_00000729
|View full text |Cite
|
Sign up to set email alerts
|

Midkine expression is correlated with an adverse prognosis and is down-regulated by p53 in oral squamous cell carcinoma

Abstract: Abstract. Midkine (MK) expression has been documented to be inversely correlated with the prognosis of patients with various tumors, but the mechanism of this relationship has not been well characterized. Recent studies have also correlated p53 expression with prognosis of patients with oral squamous cell carcinoma (OSCC). We evaluated the relationship between MK expression and clinicopathological features of patients with OSCC to clarify the influence of p53 status on MK expression in OSCC cells. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…qRT-PCR analysis showed that Brd4, Myc, and Tp53 mRNA expression increased with the progression from NILM to SCC, and each marker was significantly more highly expressed in SCC specimens than in NILM, LSIL, and HSIL specimens. These observations are in line with previous studies of OSCC [21,31,32]. For example, Wu et al [21] reported that the level of Brd4 mRNA was aberrantly upregulated in head and neck SCC samples and a 4NQO-induced OSCC animal model.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…qRT-PCR analysis showed that Brd4, Myc, and Tp53 mRNA expression increased with the progression from NILM to SCC, and each marker was significantly more highly expressed in SCC specimens than in NILM, LSIL, and HSIL specimens. These observations are in line with previous studies of OSCC [21,31,32]. For example, Wu et al [21] reported that the level of Brd4 mRNA was aberrantly upregulated in head and neck SCC samples and a 4NQO-induced OSCC animal model.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Wu et al [21] reported that the level of Brd4 mRNA was aberrantly upregulated in head and neck SCC samples and a 4NQO-induced OSCC animal model. Several studies found that c-Myc and p53 were overexpressed in OSCC tissues and TSCCA and CAL-27 cell lines, compared with their levels in normal tissues and normal human oral keratinocytes cells [31,32].…”
Section: Discussionmentioning
confidence: 99%